Rubber Seed Oil- The untapped potential source in Karnataka, India - Jayappa V; Amminally S; Patil K B; Shanbhag P K
Rubber seeds constitute 25 to 30 percent good fatty oil which is used as a major raw material in the manufacture of soaps. Karnataka with 7000 hectares of rubber plantation area and about 13 lakh trees is so far untapped for its seeds. It is expected to yield 660 tons of seeds during the current year and1290 tons by 1984-85. The seeds collected from various rubber plantation divisions were extracted for oil and the oils were analysed for their fatty acid composition by gas liquid chromatography.
Keywords: Rubber Seed; Rubber seed oil; Soap industry